Phát biểu của Chủ tịch Quốc hội Nguyễn Thị Kim Ngân bế mạc kỳ họp thứ 4, Quốc hội khóa XIV - Nguyễn Thị Kim Ngân (2017)
Phát biểu của Chủ tịch Quốc hội Nguyễn Thị Kim Ngân bế mạc kỳ họp thứ 4, Quốc hội khóa XIV ngày 24/11/2017